Modeling the effect of drug therapy on hepatitis B virus infection - Yosyingyong, Pensiri; Viriyapong, Ratchada (Food Agricultural Sciences and Technology, 2018)
With an increase in hepatitis B virus (HBV) infection every year around the world, particularly in developing countries, a mathematical model involving the relationship between HBV and the cytotoxic T lymphocytes (CTL)-mediated immunity is constructed. The model also includes non-cytolytic cure process and drug therapy of HBV. The basic reproduction number R0 is calculated and becomes threshold for equilibrium point stabilities. Sensitivity analysis is carried out to seek for potential parameters that could reduce overall spread of HBV infection. The numerical and sensitivity analyses show that both effectiveness of drug therapy in blocking new infection and non-cytolytic cure process play a key role in reducing the concentration of infected hepatocytes and free virus. Therefore, HBV drug therapy should be encouraged as one of the approaches to reduce overall chronic HBV infection.